(untitled) (Iranian Journal of Kidney Diseases, 2021)
Introduction. To explore the risk factors for development of peripheral arterial disease (PAD) in patients with maintenance peritoneal dialysis and the relationship between osteoprotegerin (OPG) and PAD. Methods. In China, 108 patients with PD were selected as the research subjects. General information such as age, gender, height, weight, BMI, blood pressure, and smoking history were collected. Serum albumin, fasting glucose, calcium, phosphorus, blood urea nitrogen, creatinine, total cholesterol, triglyceride, LDL-c, HDL-c and CRP, OPG levels were detected. Urea clearance index (Kt/V) and ankle brachial index (ABI) were measured. Results. There were 19 patients with PAD, accounting for 17.60%. Compared with the non-PAD group, the PAD group was older, female, lower BMI, a longer duration of PD, a higher proportion of diabetic patients, lower albumin and creatinine levels, lower Kt/V (renal), and higher CRP and OPG levels (P < .05); Multivariate Logistic regression analysis showed that elderly (OR = 1.262, 95% CI: 1.021 to 2.015), patients with diabetes (OR = 1.710, 95% CI: 1.054 to 2.651), low serum albumin (OR = 0.786, 95% CI: 0.651 to 0.962) and Kt/V (renal) (OR = 0.547, 95% CI: 0.366 to 0.812), high levels of CRP (OR = 1.303, 95% CI: 1.028 to 2.052) and OPG (OR = 1.125, 95% CI: 1.011 to 1.386)were independent risk factors for PAD in patients with PD; Pearson correlation analysis showed a negative correlation between OPG level and ABI (r = -0.267, P < .01). Conclusion. Old age, malnutrition, high levels of CRP and OPG, and lower Kt/V are related to the occurrence of PAD in peritoneal dialysis patients. OPG levels may be predictive indicators of PAD.